2012
DOI: 10.1002/bip.22044
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of a natural rubber from Euphorbia characias latex

Abstract: A natural rubber was identified and characterized for the first time in the latex of the perennial Mediterranean shrub Euphorbia characias. Four different methods, i.e., acetone, acetic acid, trichloroacetic acid, and Triton® X-100, followed by successive treatments with cyclohexane/ethanol, were employed to extract the natural rubber. The rubber content was shown to be 14% (w/v) of the E. characias latex, a low content compared with that of Hevea brasiliensis (30-35%) but a similar content to other rubber pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…E. characias latex has been studied with regard to its antioxidant and non-protein components ( Pintus et al, 2013 ) but several proteins have been isolated and deeply characterized ( Mura et al, 2008 ; Pintus et al, 2009 ; Pintus et al, 2011 ; Dainese et al, 2014 ; Spanò et al, in press ). It has also been identified in E. characias , a cis -prenyl transferase ( Spanò et al, 2015 ) which is the enzyme responsible of the synthesis of the natural rubber occurring in the plant latex ( Spanò et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…E. characias latex has been studied with regard to its antioxidant and non-protein components ( Pintus et al, 2013 ) but several proteins have been isolated and deeply characterized ( Mura et al, 2008 ; Pintus et al, 2009 ; Pintus et al, 2011 ; Dainese et al, 2014 ; Spanò et al, in press ). It has also been identified in E. characias , a cis -prenyl transferase ( Spanò et al, 2015 ) which is the enzyme responsible of the synthesis of the natural rubber occurring in the plant latex ( Spanò et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…В недавнем исследовании (Rzymski, 2014) для выделения каучука из кустарника гваюлы (Parthenium argentatum L.) использовали ацетон (полярный растворитель), в котором каучук не растворяется, ацетонитрил (среднеполярный растворитель) и циклогексан (неполярный растворитель), в которых каучук растворяется. Похожий подход был использован также для выделения каучука из молочая Euphorbia characias L. (Spano et al, 2012). Учитывая общую схожесть химических составов клеток растений, можно предположить, что эти методы подойдут и для кок-сагыза, к тому же в гваюле каучук, как и часть каучука в кок-сагызе, накапливается в паренхиме.…”
Section: технологии экстракции каучука из кок-сагыза для промышленностиunclassified
“…In addition, several papers report on the presence, in E. characias latex, of proteins and enzymatic activities (Barbieri et al, 1983;Palocci et al, 2003;Pintus et al, 2010;Medda et al, 2011). Moreover, antioxidants, acetylcholinesterase inhibitory activities (Pintus et al, 2013), and a natural rubber (Span o et al, 2012) have been well identified and characterized.…”
Section: Introductionmentioning
confidence: 96%